(Con) textos y silencios: la comunidad como espacio de aprendizaje no formal - Delgado Cascante, Oscar (2007)
This article is the result of a paper presented at the Youth Love Communitarian Conferences: a communitarian model of youth sexuality, which pretended to teach youth sexual education into different communities and regions of the country. The author contributes with thoughts about the experience in two different levels. First, the decision of supporting learning processes instead of teaching-learning processes, in informal education; and second, the necessity of creating synergy between learning systems.